Kynurenines as predictors of acute coronary events in the Hordaland Health Study. (15th June 2015) - Eussen, Simone J.P.M.; Ueland, Per Magne; Vollset, Stein E.; Nygård, Ottar; Midttun, Øivind; Sulo, Gerhard; Ulvik, Arve; Meyer, Klaus; Pedersen, Eva Ringdal; Tell, Grethe S.
Abstract: Background: The kynurenine pathway, the main metabolic route of tryptophan degradation, has been related to inflammatory responses. Some of its metabolites, referred to as kynurenines, have been associated with prevalence of coronary heart disease (CHD) in cross-sectional studies. This prospective study aims to investigate whether increased concentrations of kynurenines are associated with risk of acute coronary events, defined as unstable angina pectoris, acute myocardial infarction, and/or sudden death in community-dwelling elderly. Methods: The baseline examinations included 2819 individuals aged 71–74 years recruited into the Hordaland Health Study. Participants with known CHD at baseline were excluded from analyses. Baseline plasma concentrations of tryptophan, kynurenine, kynurenic acid, anthranilic acid, 3-hydroxykynurenine, xanthurenic acid, and 3-hydroxyanthranilic acid were measured by LC–MS/MS. During a median follow-up period of 10.8 years, with linkage to acute coronary event endpoints through the CVDNOR project, hazard ratios (HRs) for acute coronary events (n = 376) were estimated using Cox proportional hazard analyses. Results: After adjustment for established cardiovascular risk factors, HRs (95% CI) comparing the 4th vs 1st quartile were 1.86 (1.19–2.92) for kynurenine and 1.72 (1.19–2.49) for 3-hydroxykynurenine. Tryptophan, kynurenic acid, anthranilic acid, xanthurenic acid and 3-hydroxyanthranilic acid were not associated with acute coronary events. Conclusions: Kynurenine and 3-hydroxykynurenine were associated with increased risk of acute coronary events in community-dwelling elderly without a known history of CHD. These results suggest the involvement of the kynurenine pathway in the early development of CHD, and their potential usefulness to estimate CHD risk.